Void fraction distribution in a rod bundle with part-length rods via high-energy X-ray computed tomography - Takahiro ARAI (The Japan Society of Mechanical Engineers, 2021)
The void fraction distribution of a fuel rod bundle in a boiling water reactor is a critical parameter for accurately predicting the optimal thermal margin in the design of a reactor core. The rod bundle configuration, such as a part-length rod (PLR) and water rod, can affect void distribution. To clarify the influence of PLR on void fraction distribution, a boiling flow experiment was conducted using a 5 × 5 heated rod bundle that partially simulated a boiling water reactor (BWR) rod bundle, and three PLRs were arranged in the corner. The cross-sectional void fraction distribution was acquired using high-energy X-ray computed tomography at six height levels for wide flow conditions, system pressures of 0.1 − 7.2 MPa, inlet subcoolings of 20 - 90 kJ/kg, mass fluxes of 500 - 1250 kg/m2/s, and linear heat generation rates (LHGR) of 3.2 - 8.6 kW/m. In the PLR region, the local void fraction temporarily decreases because the PLRs disappear, and the flow channel rapidly expands. Together with the downstream PLRs, the voids propagate to the PLR region and concentrate in the center. The void fraction in the corner of the PLR region remains lower. A maximum 26% decrease in the subchannel void fraction was observed in the corner of the PLR region at the system pressure of 7.2 MPa, mass flux of 1.25 × 103 kg/m2/s, inlet subcooling of 50 kJ/kg, and LHGR of 8.6 kW/m.